A Preliminary Compilation of a Digital Video Library on Triggering Autonomous Sensory Meridian Response (ASMR): A Trial Among 807 Chinese College Students - Liu, Mengjie; Zhou, Qiang (Frontiers in Psychology, 2019)
Autonomous Sensory Meridian Response (ASMR) is a type of tingling, static-like sensation that is triggered by special audiovisual stimulation. The sensation passes through the scalp and the back of the neck, sometimes even spreading to the ends of the extremities. In recent years, research on ASMR has been gradually increasing. However, few collections of ASMR video material have been evaluated so far. In the present study, 807 Chinese participants (ASMR participants = 435, non-ASMR participants = 372) were asked to evaluate two types of ASMR videos and one control video, assessing the intensity and duration of tingling sensations triggered by these videos. A total of 60 ASMR videos were screened. The subjective assessment of the experimental group on ASMR intensity and duration, as triggered by the ASMR video material, demonstrated that the library contains 60 ASMR videos that can effectively trigger ASMR in participants who are able to experience ASMR. This video library was then subjected to a test which revealed that Cronbach’s α = 0.933. This proves that the library has good reliability, that it can effectively trigger ASMR in participants who are able to experience ASMR, and that it can be used as experimental material in future ASMR research.